Corn Production Forecast in Mexico: Implications for Food Self-Sufficiency - Talamantes-Padilla, Carlos Alberto; Zúñiga Espinoza, Nicolás Guadalupe; González-Lazalde, Iván (Technium Social Sciences Journal, 2026)
Objective: To analyze corn production data in Mexico from 1980 to 2022, using time series forecasting models to project future production trends and assess their implications for food self-sufficiency. Design/methodology/approach: The ARIMA (1,1,0) model was selected as the primary forecasting method, while SARIMAX (1,1,0) with an intercept was also considered. Production forecasts were generated up to the year 2070, with a specific focus on the year 2030. The projected production for 2030 is 27.91 million tons, with a 95% confidence interval ranging from 15.42 to 50.49 million tons. Results: The forecast suggests that per capita production will generally remain close to the average per capita consumption, with fluctuations above and below this threshold over time. Limitations on study/implications: The study does not account for additional uses of corn beyond direct consumption, which could influence self-sufficiency assessments. Future research should integrate broader economic, environmental, and policy-related factors to refine production estimates. Findings/conclusions: Corn production is expected to remain near historical consumption levels. However, a significant increase in production, approximately 13.5 million tons, is required to meet future demand and ensure food security.